Analysis Of Consumer Purchasing Patterns At Giant Atk Store Using The Apriori Method - Reza Alamsyah; Indra Sidabutar (Jurnal Info Sains : Informatika dan Sains, 2022)
Data on purchases by consumers in storage will continue to grow. So the sales application at the Atk Gyant shop is less effective. Meanwhile, in the sales transaction data, there is valuable information such as knowing a trend or pattern carried out by consumers. Data Mining has several characteristics and functions. The characteristic of data mining which aims to find tendencies in combination patterns is to use the Apriori method. The Apriori method can be applied to analyze purchasing patterns by Atk Gyant store consumers with the results of 10 patterns, namely the highest support value for 1 item is 40%, 2 items is 26% and 3 items is 19%.